The Continued Growth of Organic Agriculture: Organic 3.0 - Soto, Gabriela (2020)
The development of the organic sector in the world is divided into three sections in a timeline: Organic 1.0: the initial stages, with producers leading the process establishing ecological farming systems. There is an increase in the number of organic producers’ organizations.  Organic 2.0. Consumers willing to pay higher prices to those producers that are trying to protect the planet. The transnationals started buying small and successful organic companies. The certification process distances itself from producers and economic recognition does not reach small producers. At international forums, agroecology is recognized as the development strategy for rural areas. Organic 3.0. The movement reviews achievements of the organic sector. The global recognition of the word organic should be used to improve the impact on issues of equity, social justice, and sustainability. To achieve this, local consumption, participatory certification, real production costs that consider the environmental and health impacts of conventional production are promoted. The environmental sector must work together seeking to collaborate in the multiple areas of coincidence.